Analisis Faktor – Faktor yang Mempengaruhi Keputusan Pembelian Paket Data Internet pada Masa Pandemi - Sonia Siscabella (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2022)
The research aims to determine factor influencing consumers in the decision of purchasing an internet data during pandemic. This research is descriptive. The population is Sanata Dharma University and Atma Jaya University students. Number of sample was as many as 100 respondents. The sampling technique used was purposive sampling technique. The data collection techniques using the Q-Test Cochran analysis. The result of this research showed the factor that influenced consumers in the decision of purchasing an internet data plan were: product performance, product reliability, product durability, product ease of use, affordability, price conformity with the product, price competitiveness, advertising, sales promotion, personal selling, public relations publicity direct and data base marketing.